OPTIMIZATION ROUGHNESS LEVEL OF TURNING FROM ALUMINUM SCRAP SMELTING RESULT USING SAND CASTING METHOD - Gunawan, Indra; Muarif, M. Awal; Fadilah, Muhammad Arif; Sani, Almadora Anwar; Sampurno, Rachmat Dwi; Apandi, Khairul; Achva, RA. Jihan Ulima; Ayuni, Riski (Politeknik Negeri Sriwijaya, Indonesia, 2023)
The Production Machinery Workshop at the Sriwijaya State Polytechnic are producing a lot of aluminum scrap left over from turning, where this waste is still thrown away. This will cause pollution to the environment and will be detrimental to the Sriwijaya State Polytechnic workshop. Casting is one way to deal with aluminum scrap, scrap be melted and then reshaped into a practical material that can be reused. The use of sand as a printing medium in recycling scrolls is not recommended because it is less effective and efficient in terms of long-term use. After research has been carried out, the resulting aluminum shaving waste can be reused as practical material provided that the shavings must be separated from other waste such as iron and steel. In the optimization process, the best value is obtained at the spindle speed factor of 900 rpm (A1), then the feeding depth at 0.5 mm (B1), and the feeding speed at 0.08 mm/put. Â